1997
DOI: 10.1103/physrevlett.78.1263
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Landau Damping

Abstract: We present a new description of nonlinear Landau damping, applicable to wave propagation in a weakly collisional as well as a collisionless plasma. We derive a set of equations with a simple energy conservation law which is useful for understanding the evolution of the system. A numerical investigation shows significant differences as compared to previous studies. The reasons for the deviations from the earlier results are explained. [S0031-9007 (97)02399-5] PACS numbers: 52.35.Mw, 52.25.Dg, 52.35.Sb Wave-part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 17 publications
5
37
0
Order By: Relevance
“…The existence of BGK steady states is supported by some theoretical analysis and numerical results [21,22,23]. However, Brodin's numerical simulations [19] suggested that the wave amplitude never settles to a steady value as the energy of the resonant particles diffuses slowly into higher harmonics. Moreover Isichenko [20] argued that nonlinearities should not stop the damping of the electric field towards a vanishing time-asymptotic amplitude.…”
Section: Grand Canonical Approachmentioning
confidence: 93%
See 1 more Smart Citation
“…The existence of BGK steady states is supported by some theoretical analysis and numerical results [21,22,23]. However, Brodin's numerical simulations [19] suggested that the wave amplitude never settles to a steady value as the energy of the resonant particles diffuses slowly into higher harmonics. Moreover Isichenko [20] argued that nonlinearities should not stop the damping of the electric field towards a vanishing time-asymptotic amplitude.…”
Section: Grand Canonical Approachmentioning
confidence: 93%
“…However, this result is qualitative. Actually, in spite of major recent advances in the analytical and computational fields [19,20,21,22,23,24,25,26], mostly in the full Vlasov-Poisson framework, as well as in experiments [27], no definite answer presently exists to this intrinsically nonlinear and time-asymptotic issue, in the sense that no quantitative threshold separating nonzero time-asymptotic wave amplitude states from zero ones is known. This is basically due to the facts that analytical reductions of the problem should e.g.…”
Section: Landau Damping Of a Single Wave: Phase Transition And O'mentioning
confidence: 99%
“…This is referred to as electron beam loading or nonlinear Landau damping. [27][28][29] In fact, untrapped electrons can also gain energy ͑as seen in Fig. 1͒ and damp the wave, a process referred to as Landau damping.…”
Section: ͑4͒mentioning
confidence: 99%
“…There has been much debate in the literature [16] as to whether Landau damping leads to a stationary BGK solution [17]. This has been challenged by new simulations [18,19]. Looking at the perturbations of the BGK solutions may give new insight into this debate.…”
Section: A Stationary Spatially Inhomogeneous Plasma In Minkowski Spmentioning
confidence: 99%